Vie [compact disc] - Doja Cat, 1995- (Kemosabe / RCA, 2025)
Doja Cat's highly anticipated fifth studio album. The fifteen-track album is rich with retro textures and a sonic background charged by various influences from the '70s and '80s. It highlights Doja's own personal evolution and brings audiences into the world of love, life and the mess in between.